Substance Abuse and Gambling Behaviour among Undergraduates in Oyo State, Nigeria (Journal of Guidance and Counselling Studies, 2025)
The prevalence rates of gambling behaviour among undergraduates in Nigeria are alarming, raising serious concerns due to its strong association with substance abuse, which poses risks to their physical, emotional, and academic wellbeing. In the light of this, this study examined the relationship between substance abuse and gambling behaviour among undergraduates in Oyo State, Nigeria. The study adopted a correlational survey research design, and a total of 420 undergraduates were selected from three universities in Oyo State using a multistage sampling procedure. A research instrument, titled Substance Abuse and Gambling Behaviour Questionnaire (SAGBQ), was used for data collection, with reliability coefficients of 0.81 and 0.87. Data analysis was conducted using descriptive and inferential statistics, including percentages, Pearson Product Moment Correlation (PPMC), and Correlation Matrix. Three null hypotheses were tested at a 0.05 level of significance. The findings of the study revealed that the majority (86%) of undergraduates in Oyo State had a high level of substance abuse and 85% were involved in gambling behaviour. The study further revealed a significant predictive relationship between substance abuse and gambling behaviour among undergraduates in Oyo State (R = 0.183, p < 0.05). Further findings revealed that gender, age, place of residence, and course of study had significant predictive effects on substance abuse and gambling behaviour among undergraduates. It was recommended that undergraduates struggling with gambling problems should seek guidance and counselling, as well as other support services such as mental health services from professionals in school, as this will help to prevent incidents that could lead to substance abuse and its negative effects on their academic activities.
Keywords: gambling behaviour; substance abuse; undergraduates; Nigeria; correlational study